Continuity of export companies in the Peruvian clothing sector: An application of Multivariate Logit models - Huamanchumo de la Cuba, Luis E. (2006)
In this work, we try to find factors that determine the export continuity of Peruvian apparel exporters. Logistic regression has been used because it gives several advantages over other methods where the outcome variable is dichotomous or continuous with few values. Logit model exhibits significant interactions which have been deeply analyzed. Likewise, it was possible an exhaustive residual and goodness-of-fit analysis. Finally, we could validate the model for forecast of export continuity in 2006.